Investigation on the impact of adopting international public sector accounting standards on Financial Reporting: a case of Tsholotsho District Hospital - Ndlovu, Clever (Midlands State University, 2018)
The study sought to investigate the impact of adopting International Public Sector accounting Standards on financial reporting at Tsholotsho District Hospital. In this study fourteen staff members were used as the research subjects. Questionnaires and interviews were used as research instruments. A descriptive research method was used. The sample size was composed of three members of top management, four members of middle management, five accounting staff and two administrative staff. The data for the study was obtained from primary sources. The data was analyzed using quantitative and qualitative approach. Quantitative data was analyzed from questionnaires successful completed by use of graph, pie charts and tables. Qualitative data was analyzed using the grounded approach and summarized meanings. The study found out that Tsholotsho District Hospital was not fully complying with the provisions of the current accounting framework used and that the current framework for preparation of financial statements had weaknesses. The researcher also found out that there is need for adoption of IPSAS and equipping the staff with necessary training as to the use of the framework. The study recommends that the government should develop a roadmap and operational framework and adopt the cash basis IPSAS as its financial reporting framework. The study also recommends the government to carry out necessary trainings to all government departments. Finally, the researcher encourages further researcher should be done on a wider scope to cover the Ministry of Health and Child Care.